ANALISIS STANDAR PELAYANAN MINIMAL (SPM) PENYEDIAAN BERKAS REKAM MEDIS POLIKLINIK PENYAKIT DALAM RAWAT JALAN DI RSUD EMBUNG FATIMAH - Mulyana; Situmorang, Masriani; Wulandari, Siti (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Hospitals use Minimum Service Standards (MSS) set by the Ministry of Health to provide health services to the community. Community service activities were carried out at Embung Fatimah Hospital Batam with counseling on SPM for the provision of medical record files. This activity went smoothly and the participants were very enthusiastic. The material was delivered by the team who explained the SPM for medical record files according to the Permenkes regulations. Socialization and training related to SPM for medical record files have also been carried out at Embung Fatimah Hospital Batam. The solution needed is socialization and monitoring of discipline in the provision of medical record files so as not to hamper other work, especially in the medical record file storage section.